Mangrove Identification on the Rainbow Bridge Coastal Coast Lamundre Village, Watubangga District, Kolaka Regency - Dina Nurhayati; Sutriani Kaliu; Saparudin Saparuddin (Journal of Biological Science and Education, 2022)
The village of Lamundre is an area overgrown with a mangrove ecosystem of 4 hectares and is well developed on the coast. The area can be well overgrown with mangroves because of environmental conditions and other supporting factors such as muddy substrate, muddy sand in tidal transition areas, salty, brackish water and the presence of currents/waves that are classified as mangrove growing conditions. This study aims to determine the types of mangrove plants and environmental parameters on the abundance of mangrove species on the coast of the Rainbow Bridge, Lamundre Village, Watubangga District, and Kolaka Regency. This type of research is descriptive and qualitative by using mangrove samples on the roots, stems, leaves, flowers and fruit. The method used is Line Transect, which uses plots that are aligned on the main line (Basseline) that has been determined in the research area along 280m, the total number of plots is 10, with each plot of 10m x 10m. Based on the study's results on the identification of mangroves in the Pantai Pelangi Beach, Lamundre Village, Watubangga District, and Kolaka Regency, it shows that mangroves belong to 2 families and 7 species. The mangroves are from the Rhizophoraceae family namely Rhizophora mucronata species, Rhizophora apiculata, Rhizophora stylosa, Ceriops decandra, Bruguira cyndrica, Bruguira ghymnorryza and the Soneratiaceae family namely Soneratia caseolaris. Keywords: Lamundre village, identification, mangrovee